The tropical African tribes Poreuomenini, Zeuneriini and Morgeniini with the description of a new genus (Orthoptera: Tettigoniidae: Phaneropterinae) - Massa, Bruno (Zootaxa, 2018)
Species currently considered belonging to the tribe Poreuomenini Brunner von Wattenwyl, 1878 are here separated; only Poreuomena Brunner von Wattenwyl, 1878 and Cestromoecha Karsch, 1893 remain in the tribe Poreuomenini, while Zeuneria Karsch, 1889 and Gravenreuthia Karsch, 1892 are transferred to the new tribe Zeuneriini Karsch, 1890. Morgenia Karsch, 1890 and Mangomaloba Sjöstedt, 1902 are moved to the new tribe Morgeniini Karsch, 1890. The new genus and species Paraporeuomena signata is described from the Tri National Sangha (TNS) (Central African Republic) and tentatively considered belonging to the tribe Poreuomenini. Its general aspect is hardly similar to that of the genus Poreuomena Brunner von Wattenwyl, 1878, but it differs remarkably in the shape of eyes, that are oval and elongate, in the presence of subocular grooves, of spines on genicular lobes of femora, and of ventral spines on fore and mid legs. Differently from Poreuomena the last tergite is not modified.